2018
DOI: 10.1021/acs.jpcc.7b11512
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Vacancy Formation and Water Adsorption on Reduced AnO2{111}, {110}, and {100} Surfaces (An = U, Pu): A Computational Study

Abstract: The substoichiometric {111}, {110} and {100} surfaces of UO2 and PuO2 are studied computationally using two distinct yet related approaches based on density functional theory; the periodic electrostatic embedded cluster method (PEECM) and Hubbard-corrected periodic boundary condition DFT. First and second layer oxygen vacancy formation energies and geometries are presented and discussed; the energies are found to be substantially larger for UO2 vs PuO2, a result traced to the substantially more positive An(IV)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
46
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 68 publications
17
46
1
Order By: Relevance
“…Recent studies found that the oxygen vacancy formation energies are correlated with the reduction potential of An 4+ , in accordance with the f -band energy drops as going down the actinide series [53,56]. Interestingly, the fundamental question regarding the relative stability of oxygen vacancy in the top-surface and subsurface is still debatable, although similar DFT + U calculations were used [53,54]. The conclusions for PuO 2 (111) surface are consistent that the oxygen vacancy formation energy is slightly lower in the top-surface than in the subsurface in previous studies [44,53], and the energy difference is within 0.05 eV.…”
Section: Theoretical Calculationssupporting
confidence: 54%
See 2 more Smart Citations
“…Recent studies found that the oxygen vacancy formation energies are correlated with the reduction potential of An 4+ , in accordance with the f -band energy drops as going down the actinide series [53,56]. Interestingly, the fundamental question regarding the relative stability of oxygen vacancy in the top-surface and subsurface is still debatable, although similar DFT + U calculations were used [53,54]. The conclusions for PuO 2 (111) surface are consistent that the oxygen vacancy formation energy is slightly lower in the top-surface than in the subsurface in previous studies [44,53], and the energy difference is within 0.05 eV.…”
Section: Theoretical Calculationssupporting
confidence: 54%
“…E O 2 is the total energy of one isolated O 2 molecule in its ground state. From these calculations, it is seen that the oxygen vacancy formation energies decrease from ThO 2 to PuO 2 [44,[53][54][55]. Recent studies found that the oxygen vacancy formation energies are correlated with the reduction potential of An 4+ , in accordance with the f -band energy drops as going down the actinide series [53,56].…”
Section: Theoretical Calculationsmentioning
confidence: 68%
See 1 more Smart Citation
“…There has been some debate in the literature as to whether the first monolayer of water is adsorbed molecularly or dissociatively on the defect-free AnO2 {111} surface or its LnO2 analogues. Bo et al 24,25 suggest a mixture of molecular and dissociative adsorption on UO2 and NpO2 {111} surfaces whereas Molinari et al 26 24,25 and by Molinari et al 26 , as well as recent work by our group, 3 suggest dissociative adsorption is preferred in the vicinity of oxygen vacancies on all three surfaces.…”
Section: Resultsmentioning
confidence: 88%
“…It is essential that we fully understand the causes of the container distortions and, as experimental measurements are extremely challenging, computational approaches have a very valuable role. As part of this project, we have previously considered the adsorption of up to a monolayer of water on stoichiometric 1,2 and reduced 3 low Miller-index surfaces of the actinide oxides UO2 and PuO2, using density functional theory, within both periodic boundary condition (PBC) and embedded cluster frameworks. In this contribution, we report our PBC investigations of the adsorption of multiple layers of water on the same low-index surfaces of UO2 and PuO2, as there is experimental evidence for multiple water layers adsorbed onto PuO2 4 , as well as on other metal oxides.…”
Section: Introductionmentioning
confidence: 99%